2020
DOI: 10.1002/hep.30928
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Stress Increases Expression of Yes‐Associated Protein and Transcriptional Coactivator With PDZ‐Binding Motif in Hepatocytes to Promote Parenchymal Inflammation and Fibrosis

Abstract: Background and Aims Activated hepatocytes are hypothesized to be a major source of signals that drive cirrhosis, but the biochemical pathways that convert hepatocytes into such a state are unclear. We examined the role of the Hippo pathway transcriptional coactivators Yes‐associated protein (YAP) and transcriptional coactivator with PDZ‐binding motif (TAZ) in hepatocytes to facilitate cell–cell interactions that stimulate liver inflammation and fibrosis. Approach and Results Using a variety of genetic, metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 49 publications
(64 reference statements)
4
123
0
Order By: Relevance
“…In human umbilical vein endothelial cells, overexpression of YAP induces expression of a set of pro-inflammatory genes, such as IL-6, VCAM1, and ICAM1 [ 45 ]. Likewise, hepatocyte-specific overexpression of YAP in mice upregulates the expression of inflammatory factors, including IL-1β and TNFα [ 46 ]. Thus, YAP may directly regulate a set of genes related to immune and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In human umbilical vein endothelial cells, overexpression of YAP induces expression of a set of pro-inflammatory genes, such as IL-6, VCAM1, and ICAM1 [ 45 ]. Likewise, hepatocyte-specific overexpression of YAP in mice upregulates the expression of inflammatory factors, including IL-1β and TNFα [ 46 ]. Thus, YAP may directly regulate a set of genes related to immune and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, overexpression of hepatocyte TAZ is sufficient to drive NASH progression, whereas TAZ silencing attenuates inflammation and fibrosis ( 149 ). Hepatocyte Hippo pathway activity also upregulates expression of the pro-inflammatory and pro-fibrotic gene, Cyr61/CCN1 , which is highly expressed in livers of NASH patients ( 205 ).…”
Section: Potential Of Fibroblast Growth Factor 21 Physiology As a Thementioning
confidence: 99%
“…Evidence has been shown that YAP is a core component of the Hippo pathway, which could promote inflammation response in hepatocytes (Mooring et al 2019). Zhou et al indicated that YAP could aggravate inflammatory bowel disease via promoting M1 macrophage polarization (Zhou et al 2019a).…”
Section: Is Activated Yap Signaling In Lps-stimulated Macrophagesmentioning
confidence: 99%